2021
DOI: 10.1177/20539517211046374
|View full text |Cite
|
Sign up to set email alerts
|

Data access and regime competition: A case study of car data sharing in China

Abstract: We study the case of a Chinese industrial policy, implemented in Shanghai that makes it mandatory for car manufacturers to share electro-mechanical performance and real time navigation data from their entire fleet of electric and hybrid vehicles with local and central government authorities. This policy seeks to prevent fraud in state subsidies, reduce emissions, assess the performance of New Energy Vehicles and strengthen the competitiveness of Chinese manufacturers of these vehicles. We argue that economies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Smith et al feature the developing dependence on the prescient investigation, which uses authentic information to conjecture future client ways of behaving, market patterns, and mission results [5]. Besides, Johnson and Zhao accentuate the reconciliation of ongoing investigation, empowering organizations to answer quickly to changing business sector elements [6]. Be that as it may, these approaches are progressively tested by the volume and intricacy of information, as indicated by Brown, requiring all the more impressive and productive registering arrangements [7].…”
Section: Current Trends and Methodologies In Marketing Analyticsmentioning
confidence: 99%
“…Smith et al feature the developing dependence on the prescient investigation, which uses authentic information to conjecture future client ways of behaving, market patterns, and mission results [5]. Besides, Johnson and Zhao accentuate the reconciliation of ongoing investigation, empowering organizations to answer quickly to changing business sector elements [6]. Be that as it may, these approaches are progressively tested by the volume and intricacy of information, as indicated by Brown, requiring all the more impressive and productive registering arrangements [7].…”
Section: Current Trends and Methodologies In Marketing Analyticsmentioning
confidence: 99%
“…Creemers (2019) details the example of the Joint Laboratory for Intelligent Command and Control Technologies, established jointly by Baidu and the state-owned defence firm the China Electronics Technology Group (CETC) aimed at upgrading the Chinese military's information warfare capabilities. More significant than direct military involvement in the platform economy, however, is how MCF signals an increasing expectation that platforms cooperate with state agencies for purposes of economic statecraft – with broad applications from urban and transport planning to personal security measures (e.g., Bloomberg, 2021, Martens and Zhao, 2021). Indeed, this expectation underpinned an industry-wide regulatory storm following the decision to block Ant Financial's US IPO in November 2020.…”
Section: Chinese and American Varieties Of Spcmentioning
confidence: 99%
“…The literature under review showed that few public sector organizations structurally collaborate with others on activities and information sharing (Klievink et al, 2017; Martens and Zhao, 2021; Micheli et al, 2020; Vezyridis and Timmons, 2017). There are examples of best practices, such as US governments sharing code on GitHub (Mergel, 2015), or Italian municipalities setting up a collaborative network for welfare services (Bonomi et al, 2020), but these remain the exception rather than the rule.…”
Section: Findings Of the Systematic Literature Reviewmentioning
confidence: 99%